2016
DOI: 10.1108/bfj-06-2015-0200
|View full text |Cite
|
Sign up to set email alerts
|

Urban agriculture: connecting producers with consumers

Abstract: Purpose – Urban farming is becoming more common in the USA, as food-based entrepreneurs seek to make money farming in the city. Yet many urban farms are concerned with other factors in addition to food production, and thus have incorporated social goals into their missions. The purpose of this paper is to identify the social missions of urban farms in the USA, their extent, and explores differences and similarities among farms with varying missions. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 28 publications
1
44
0
2
Order By: Relevance
“…Urban farms report diffi culties paying decent wages and rely heavily on unpaid labor (Biewener, 2016 ;Cohen & Reynolds, 2015 ). A 2012 survey of 370 urban farmers working in or around the United States found that roughly two-thirds were failing to make a living, reporting sales of less than $10,000 per year (Dimitri, Oberholtzer, & Pressman, 2016 ). The study authors note that many urban farms rely on grant funding, donations, and off-farm income to support their farm ventures.…”
Section: The Social Benefi Ts Of Urban Agriculturementioning
confidence: 95%
“…Urban farms report diffi culties paying decent wages and rely heavily on unpaid labor (Biewener, 2016 ;Cohen & Reynolds, 2015 ). A 2012 survey of 370 urban farmers working in or around the United States found that roughly two-thirds were failing to make a living, reporting sales of less than $10,000 per year (Dimitri, Oberholtzer, & Pressman, 2016 ). The study authors note that many urban farms rely on grant funding, donations, and off-farm income to support their farm ventures.…”
Section: The Social Benefi Ts Of Urban Agriculturementioning
confidence: 95%
“…Marketing channels in the cereals sector are a dynamic category to be viewed through the lens of structural changes occurring among agri-producers themselves, as well as among wholesalers and retailers as key players in the food supply system (Dimitri et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Previous survey work in the Bay Area recorded high yielding production systems that provides further evidence for the important contributions of urban farms to local food security [23]. Many UA organizations dedicated to educational and food security objectives are also deeply tied to food justice initiatives, reflecting associations to important regional social movements [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…These farms operate with different organizational patterns and structures, including farms that are collectively managed and harvests equitably distributed; allotment style farms where each farmer has their own plot; production-based operations; or a hybrid of these schemas. Operations are often dependent on outside funding as sales commonly do not generate enough income to be self-sufficient [12]. With little funding and support, UA is expected to meet ambitious social goals while being financially sustainable [13].…”
Section: Urban Agriculture Persistsmentioning
confidence: 99%